The Berenstain Bears in the dark - Berenstain, Stan, 1923-; Berenstain, Jan, 1923- (New York : Random House, 1982)
When Brother Bear brings a spooky book from the library, bedtime and the dark become ominous and threatening to Sister Bear
AD 690
Adult 690
Accelerated Reader AR
Keywords: Night -- Fiction; Fear -- Fiction; Bears -- Fiction